2021
DOI: 10.1002/mnfr.202100164
|View full text |Cite
|
Sign up to set email alerts
|

Novel Relationship Between Plasmalogen Lipid Signatures and Carnosine in Humans

Abstract: Introduction: Carnosine is a naturally occurring dipeptide abundant in the skeletal and cardiac muscle and brain, which has been shown to improve glucose metabolism and cardiovascular risk. This study showed that carnosine supplementation had positive changes on plasma lipidome. Here, this study aimed to establish the relationship of muscle carnosine and serum carnosinase-1 with cardiometabolic risk factors and the lipidome. Methods and Results: This study profiles >450 lipid species in 65 overweight/obese non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…As for body nutrition parameters, overweight (BMI≥24kg/m 2 ) and non-sarcopenic patients had relatively high Metabolites-Score, though without significant difference due to low sample size. Several studies reported that overweight and sarcopenic patients had distinctive lipidomic signatures like dysregulated SM and PC lipid species (31)(32)(33). Interestingly, our results found that NLR, an inflammatory marker, was significantly related to Metabolites-Score.…”
Section: Discussionsupporting
confidence: 46%
“…As for body nutrition parameters, overweight (BMI≥24kg/m 2 ) and non-sarcopenic patients had relatively high Metabolites-Score, though without significant difference due to low sample size. Several studies reported that overweight and sarcopenic patients had distinctive lipidomic signatures like dysregulated SM and PC lipid species (31)(32)(33). Interestingly, our results found that NLR, an inflammatory marker, was significantly related to Metabolites-Score.…”
Section: Discussionsupporting
confidence: 46%
“…Glycated hemoglobin (HbA1c) was determined by high-performance liquid chromatography (ADAMRA1c HA-8180V, ARKRAY, Inc., Kyoto, Japan). Insulin sensitivity (M-value) was assessed using the euglycemic-hyperinsulinemic clamp and was defined as the weight-adjusted glucose infusion rate during the last 30 min when a steady-state was achieved [ 35 ]. The main anthropometric and clinical variables are described in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, our study for the first time found an association between circulating neutrophils/lymphocyte counts and CN-1 levels in diabetic patients. Although the underlying mechanism to explain the correlation is not fully clear, it seems that inflammatory processes might affect serum CN-1 as also suggested by others (MaynerisPerxachs et al 2021). In keeping with current knowledge of CN-1 in the context of diabetes and low-grade inflammation, further studies are warranted to reinforce the role of CN-1 herein.…”
Section: Discussionmentioning
confidence: 60%
“…Since carnosine may alleviate inflammation as previously reported (Fleisher-Berkovich et al 2009;Liu et al 2020), a correlation between pseudoinflammatory variables and the carnosine degrading enzyme in the Chinese Han population was unexpected. A correlation between low-grade inflammation and serum CN-1 expression has been recently suggested in obese non-diabetic individual (MaynerisPerxachs et al 2021).…”
Section: Discussionmentioning
confidence: 93%